PERANCANGAN VIDEO PROMOSI GROUP KESENIAN TRADISIONAL HASAN HUSEN LUKAH GILO - ASTARIDO BERNANDA, Hendra Ariwan, S.Sn., M.Sn Dr. Syafwandi, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
This article was written with the aim of producing a form of promotion of the Hasan Husen Lukah Gilo traditional arts group effectively and efficiently, this design uses video media and is disseminated by uploading it on social media in order to reach broad targets. thus the video promotion of Hasan Husen Lukah Gilo traditional arts group can show an interesting performance from the traditional Hasan Husen Lukah Gilo art group to the target audience. The method used in collecting there are two parts, namely by collecting primary data and secondary data. Then proceed with the method of data analysis using 5W + 1H analysis, namely: what, who, when, where, why, and how.The design of this promotional video can create a good positioning. In addition, it can attract the attention of the target audience, especially the people who come to the city of Padang, considering that audio-based promotional media is a medium that is very likely and has a big influence in increasing promotion coupled with supporting media such as posters, motion posters, stickers, key chains, hats, clothes t-shirt, and Cd cover .Keywords : Designing, Lukah Gilo, Promotional, Videos.